(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The principle of an interview requires revenues to expenditures by linking the efforts and achievements and disclosure sufficient to result activity, in the case generate future benefits of a particular asset, this asset appears in the balance sheet to reflect with the rest of the accounting unit’s assets on the strength of financial position In the absence of future benefits from the effort are so loaded effort on the result accounts that reflect the outcome of activity during a specific period if the month or be separated or fiscal year. The researcher reached the following conclusions: 1- difficult to control the cash inflows and outflows as a result of the multiplicity of sources of funding. 2- weak financial controls and procedures carried out by the Federal Office of financial supervision as a result of the spatial separation between the point of spending and the beneficiary. The most significant recommendations: 1-The need to limit spending on self-financing of the operating and investment budgets institutions. 2- the necessity of activating the role of the Federal Audit Court in regard to cross-check of projects by teams working in different institutions.